The fundamental determinants of protest participation: evidence from Hong Kong’s antiauthoritarian movement - Cantoni, D; Heizlsperger, L-J; Yang, DY; Yuchtman, N; Zhang, YJ (Elsevier, 2022)
Which fundamental traits are associated with individuals’ participation in antiauthoritarian protests? We conduct a series of surveys eliciting participation in Hong Kong’s antiauthoritarian movement, covering a period that included protests ranging from tens of thousands to over one million participants. For a sample of university students, we construct a comprehensive profile of fundamental economic preferences: risk and time preferences plausibly affecting an individual’s costs of protest participation; social preferences affecting the benefits. We also elicit other fundamental traits: personality, cognitive abilities, and socioeconomic background. We document several facts about protest participants: (i) fundamental economic preferences, particularly risk tolerance and pro-social preferences, are the strongest predictors of protest participation; (ii) the strongest predictors are the same for modest and massive protests, with larger effects for massive protests; (iii) participation in massive protests is not driven by marginal types, but rather by inframarginal types; (iv) both the distribution of fundamental preferences and their relationship with protest participation are very similar between university students and the broader population; and, (v) willingness to respond honestly to sensitive survey questions is high and stable over the entire sample period. Our findings suggest that economic preferences be considered alongside class background and personality as deeply determined traits driving protest participation and can inform the development of dynamic models of protest movements.